TARIFF OPTIMIZATION USING ACTIVITY BASED COSTING METHOD (A CASE STUDY OF TELKOM INFRASTRUCTURE ASSURANCE UNIT BANDUNG) - Mochammad Taufiq, Reza
At the end of 2018, the Infrastructure Assurance (IAS) Unit, one of the many units under PT Telkom Indonesia, faced with an urge to revise their tariff formulation. Previously, the IAS Unit is not too concerned about tariff charged because as a support-oriented unit, funding is borne by the investment committee of the main company. The difficulties in asking for funding in the recent year makes the unit become more aware of the tariff charged to the customer. Then, after an in-depth analysis of the problem using 5-whys technique, it was found that the solution to the problems faced by the unit is by updating the calculation formulation of the tariff that will be charged to the customers that has not been revised since 2016. To assist in designing the formulation of the tariff calculation, internal analysis is carried out by using resources and capabilities, while the external analysis using Porter's five-forces and also customer analysis. From the two analyzes, it was found that the Infrastructure Assurance unit had the resources and ability to successfully perform the strategy to revise the tariff formulation that can be accepted by other parties. Finally, the method used to make the formulation of the new testing tariff calculation that is relevant will use the activity-based costing method, where the formulation takes into account the use of each test equipment, human labor, and time spent. In using activity-based costing method, there are several cost aspects that will be used to support the method such as direct equipment costs and personnel costs which are part of direct costs, equipment maintenance costs and environmental costs that are part of indirect costs, and additional costs that are part of both direct and indirect costs. The five cost components will be included in the activity-based costing calculation. The results of the calculations that has been executed by using the activity-based costing method found that the total test rate changes against 26 types of telecommunications devices reaches 18.30%. The tariff increase received a positive response from the management of the Infrastructure Assurance unit. Later, after adjustments are made, it is expected that the new test tariff calculation can help the Infrastructure Assurance unit to be able to run and continue the business in telecommunication devices testing and certification without constraints.